A High Incidence of Multidrug Resistant Strains as the Agents Causing Bloodstream Infection in Hospital in Indonesia - Suryawati, Betty; Saptawati, Leli (Indonesian Journal of Medicine, 2019)
Background: Various bacteria have been identified as the agents causing bloodstream infection. Multidrug resistant (MDR) strains, such as Gram-negative pathogens producing extended-spectrum beta-lactamases (ESBL) and Methicillin-resistant S.aureus (MRSA) are potential bacterial agents causing bloodstream infection in the hospital setting. The increase of these MDR strains in bloodstream infection is alarming since there are limited antibiotic choices for treatment. This study aimed to investigate the agents causing bloodstream infection and to investigate their antibiotics susceptibility profiles. Subjects and Method: Samples were venous blood collected from patients admitted to hospital from January 2014 to December 2016. Bacteria were grown in-automated BACTEC® blood culture (BD, New Jersey, USA). The identification of MRSA strain was conducted using oxacillin susceptibility test. The bacterial identification and identification of ESBL-producing bacteria was conducted using colorimetric assay using Vitek2®system (bioMérieux).Results: The antibiotic profiles of all bacteria isolated from venous blood samples were analysed. The most bacteria isolated from the blood stream were K. pneumonia, A. baumannii, E. coli, P. Aeruginosa, E. cloacae, S. marcennes, S. haemolyticus, S. hominis, S.epidermidis, and S. aureus. Conclusions: The resistant profiles of bacteria isolated from blood stream showed that there was a high incidence of MDR bacteria, including potential ESBL-producing bacteria, carbapenemase-producing bacteria and MRSA strains.Keywords: Bloodstream Infection, Staphylococcus aureus, Extended Spectrum Betalactamase, Antibiotic Resistance.Correspondence: Betty Suryawati. Department of Microbiology, Faculty of Medicine, Universitas Sebelas Maret, Jl. Ir. Sutami No 36A, Surakarta 57126, Central Java, Indonesia. Email: betty.suryawati@staff.uns.ac.id.Indonesian Journal of Medicine (2019), 4(1): 28-34https://doi.org/10.26911/theijmed.2019.04.01.05